AS RELAÇÕES ENTRE SATISFAÇÃO NO TRABALHO, COMPROMETIMENTO ORGANIZACIONAL AFETIVO E INTENÇÃO DE ROTATIVIDADE: UM ESTUDO EM UMA MINERADORA DE DIAMANTES EM ANGOLA - Francisco, João Domingos da Silva (2013)
Much has inquired about the antecedents of turnover intention. Among the possible variables with ability to relate to plans of employees leaving the organization stand out, job satisfaction and affective organizational commitment. The present study aimed to analyze the relationship between these three variables, job satisfaction, affective organizational commitment and turnover intention . Linking objectives through its internal or external stimuli, unraveled in the study in a diamond-mining in Angola where we analyzed the relationships between the three variables. 151 employees participated in the survey, all of Angolan nationality, randomly selected in different areas of the same company. After questionnaires with this three validated measures and accurate processing of the date, all numerical in nature, was processed by the software Statistical Package for the Social Sciences SPSS, version 19.0 for Windows. It was found that the mean age of participants was 38.34 (SD = 8.42) years, mostly male, unmarried, with complete secondary school, not exercising management positions, belonging to the group (GP III) a total of 89 (58.9%), doing much of his work with another person or group, with working time ranging from 1 (one) to 16 years. The descriptive results indicate that workers hold a picture of job satisfaction, satisfaction with the largest proportionate number of times and opportunities to be promoted with the professional capacity of their leaders, foud in understanding each other and the way they are treated by their heads, and lower with the kind of friendship, trust and spirit of cooperation demonstrated by their colleagues, as well as the ability absorbed and salary compared to how it works. The framework of affective organizational commitment, shows greater affection issues the company in making the employee fell proud of it and happy with it, as the slightest affection related issues fell enthusiastic about her and interested in her. Correlation analysis by Pearson s r indices reported negative and significant between the two variables and turnover intention. These results stated that the plan to leave the company where they work and less and less as they raise levels of job satisfaction and affective organizational commitment.